Hydro-thermal performance of CNT nanofluid in double backward facing step with rotating tube bundle under magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
In this study, a novel method for convective heat transfer control of flow past a double backward facing step with combined effects of oriented magnetic field, rotating tube bundle and inclusion of highly conductive CNT nanoparticles in the base fluid is offered. Hydro-thermal performance assessment of double backward facing step is numerically performed with finite volume method in laminar flow regime. Effects of Reynolds number, rotational Reynolds number, circular cylinder arrangement and horizontal local of the tube bundle, distance between the steps and magnetic field strength on the fluid flow, heat transfer, pressure drop and hydro-thermal performance coefficient variation are examined. The rotation of the cylinder, arrangement and location were found to alter hydro-thermal performance while the average Nu is enhanced with higher Reynolds and Hartmann numbers. The presence of the upper vortex location resulted in higher deflection of the main stream toward the hot bottom wall which resulted in higher local heat transfer rates. This is especially the case for clockwise direction rotation at the height speed and local Nu value increment is 244% as compared to non-rotating cylinder case. Best performance coefficient is obtained with MHD flow at Hartmann number of 5 while performance increase is 13% as compared to non-magnetic field configuration. The vertical size and location of the upper vortex changes with the horizontal location of the tube bundle and spacing between the steps. As compared to reference configurations, variations in the hydrothermal performance coefficients are 15% and 20% when varying the horizontal location and distance between the steps. The CNT nanoparticles inclusion in the base fluid resulted in performance coefficient enhancement of 52% at the highest solid volume fraction. As flow separation and subsequent attachments are encountered in a variety of heat transfer engineering applications, the results of the present work will be helpful in the design and optimization of various thermal engineering systems.
Keywords: Tube bundle; Rotating cylinder; Finite volume method; MHD flow; Hydrothermal performance; Double backward facing step